Social and spatial organisation – assessing the agroecological changes on farms: case study in a banana-growing area of Guadeloupe. (1st January 2011) - Houdart, M.; Bonin, M.; Compagnone, C.
The aim of the present study is to assess the individual and collective agroecological changes of farmers located in the same drainage basin in Guadeloupe. Farmers of this basin were interviewed; sociogrammes were drawn up and correlated with the farm distribution in the study area. The network analysis combined with the spatial configuration analysis highlighted how the geographical area had an impact on interactions between farmers, and how the extent of the local dimension of these interactions governed some exchanges. We revealed also how alternative production orientations seemed to be introduced within the network so as to facilitate change while preserving some social structural stability. This indicates that new strategies should be introduced by providing farmers with technical training that stresses both technical and social efficiency.